The Role of Law in Supporting Secondary Uses of Electronic Health Information. Issue 1 (March 2015) - Ramanathan, Tara; Schmit, Cason; Menon, Akshara; Fox, Chanelle
<x xml:space="preserve">Abstract</x> Law establishes the foundation for the "secondary use" of electronic health information (EHI) for public health purposes. Federal law, state law, and legal tools, such as contracts and policies, support data exchange between providers, facilities, and public health departments. This article describes the legal landscape surrounding secondary use of EHI.